Vienna: View from the Biber bastion - Batty, Robert, 1789-1848 (artist):::Creator::::::::::::; Findin, Edward Francis, 1791-1857 (engraver):::Contributor:::::::::::: (London; Rodwell & Martin; United Kingdom)
Color engraving of Vienna viewed from the Biber bastion